Relation of Antiulcer Effect of Progesterone Resulting from Follicle Stimulating Hormone Inhibition with Gastric Cyclooxygenase Levels in Female Rats - Karaca, Mehmet; Borekci, Bunyamin; Kumtepe, Yakup; Salman, Suleyman; Hacimuftuoglu, Ahmet; Gulaboglu, Mine; Bilici, Mehmet; Dursun, Hakan (Asian Journal of Chemistry, 2010)
Sex hormones have detrimental effects as well as beneficial ones. This study investigated effects of acute and chronic administration of progesterone and follicle stimulating hormone (FSH) on gastric ulcers and cyclooxygenase (COX) enzyme levels. Chronic progesterone at low doses (0.5 and 1.0 mg/kg), which did not stimulate PRs, reversed the reducing effect of FSH in gastric COX-1 level and decreased FSH-stimulated indomethacin ulcers by inhibiting FSH. Progesterone was observed to decrease COX-1 and increase ulcer area at dosages which stimulated PRs (3 mg/kg). FSH decreased COX-1 levels in gastric tissue via PRs. Mifepriston prevented the detrimental effects of progesterone and FSH in gastric tissue. Also inhibitory effects of 3 mg/kg progesterone on gastric COX-2 level were reversed by mifepriston. In conclusion low dose of chronic progesterone that inhibited FSH was beneficial in case of increasing gastroprotective COX-1 activity and healing indo-methacin induced gastric ulcers.